A survey of the quality of maternity care at the Norfolk & Norwich University Hospital NHS Foundation Trust. (16th November 2010) - Ifionu, J; Hamouda, T; Saleh, M
Abstract : This study was planned to assess the quality of maternity care provided in a busy teaching maternity unit. An anonymous questionnaire based on the Royal College of Obstetricians and Gynaecologists (RCOG) standards of maternity care document (2008) was distributed among all women delivered at Norfolk and Norwich University Hospital between February and July 2009.1 Women who delivered stillbirths and babies in a very poor condition were excluded. The questionnaire included 11 questions based on the RCOG standards and included a space for free comments. The authors received responses from a total of 302 patients. The data were spread and analysed using Microsoft Excel and the patients comments were studied using a combination of content and thematic analysis. The survey showed that 90% of patients did not think that prepregnancy counselling was important and only 4% was offered such a service. 42% of women did not develop their own care plan during pregnancy. The majority of patients were satisfied with the care they received. However, 21% of patients rated the community care as poor. Hospital care during pregnancy, labour and during postnatal period was rated as poor by 11–13% of patients. 65% of patients did not receive postnatal advice about contraception. 47% of patients added their own comments were 62% were positive, 18% negative and 20% were mixed. The comments covered three areas: level of care, staff and facilities. Although the survey in general showed a positive picture, still there is a lot of room for improvement.